Digital Literacy Educational Visual Media Parenting Child Pornography - Nezahwa Fibriana (CV. Uruboros Publishing Group, 2025)
The increasingly massive development of digital technology brings both positive impacts and serious challenges to children's growth and development, one of which is the increased risk of exposure to pornographic content. Easy access, minimal digital literacy, and weak supervision are factors that increase children's vulnerability to content that is inappropriate for their psychological and cognitive developmental stages. This study aims to examine preventive efforts to protect children from exposure to pornography in the digital era through the synergy of parental roles and the use of educational visual media, particularly posters. The research method used is a qualitative approach through literature review by reviewing journal articles, research reports, and relevant documents discussing digital parenting, the dangers of pornography on children's brains, and educational visual media. The discussion focuses on two main aspects: the role of parental care in building children's control, communication, and digital literacy, and the effectiveness of educational visual media as a communicative and easily understood preventive tool for children and students. The results of the study indicate that the collaboration between adaptive parenting and the use of educational visual media can strengthen children's and their surrounding environment's awareness of the dangers of pornography. This research is expected to serve as a reference for parents, educators, and education practitioners in designing sustainable and contextual prevention strategies in the digital era.